Trends in ammonia measurements in the Netherlands over the period 1993–2014. (January 2017) - van Zanten, M.C.; Wichink Kruit, R.J.; Hoogerbrugge, R.; Van der Swaluw, E.; van Pul, W.A.J.
Abstract: We present measurements of atmospheric concentrations of ammonia and ammonium in the Netherlands over the period 1993–2014 and measurements of wet deposition of ammonium for 1985–2014. The various time series have been obtained at 16 monitoring stations from the Dutch National Air Quality Monitoring Network. The monitoring stations are geographically homogenously spread over the Netherlands and are equally distributed over regions with relatively low, moderate and high ammonia emission. During the period covered, changes in the monitoring have occurred. To obtain consistent time series, data are revalidated or corrected when necessary, according to current validation procedures or latest technical insights. The time series of ammonia concentrations are gap filled and time series corrected for meteorological influences are constructed. The course in the ammonia concentrations shows roughly two periods. For 1993–2004, the ammonia concentrations show a downward trend of 36%, which is statistically significant with a confidence interval (CI) of 99%. For 2005–2014, an upward trend of 19% (CI 90%) is reported. Correcting time series of ammonia concentrations for meteorological influences enhances the statistical reliability of the derived trends. This resulted in trends of −40% (CI 99%) and 24% (CI 95%) respectively. For the full period there exists no trend in ammonia concentrations due to a trend in atmospheric conditions. For 2005–2014 ammonia concentrations increased especially in springtime, while showing no change in winter months. After correcting for meteorological influences, all seasons in this period show an increase in ammonia concentrations although the increase in the spring months is still the largest. For 1993–2014 the reported ammonia emissions in the Netherlands declined in both periods with respectively 51% and 22%. The trends in emissions and ammonia concentrations correspond in the period 1993–2004 whilst over the period 2005–2014, the trends in emissions and concentrations of ammonia diverge. This divergence is for roughly a third accounted for by processes related to changes in chemical climate (see accompanying modelling paper by Wichink Kruit et al., 2016) but it is not clear what explains the remaining difference in trends. For 1993–2014, downward trends of wet deposition of ammonium and ammonium in aerosol are found to be 47% and 68%, respectively. A split into two periods is not found as is the case with the ammonia concentration. However, although statistically not significant, both wet deposition of ammonium and ammonium in aerosol show a leveling off in decline between 2005 and 2014. Highlights: Trends in observed ammonia and reported emissions between 1990 and 2004 are consistent. Trends between 2005 and 2014 diverge: emissions further decline but concentrations rise. Trends in ammonium in aerosol and precipitation do not match the trends in ammonia. No trend in ammonia exists due to a trend in meteorological conditions.